2015
DOI: 10.1007/s11032-015-0348-8
|View full text |Cite
|
Sign up to set email alerts
|

Marker-assisted introgression of bacterial blight and blast resistance into DRR17B, an elite, fine-grain type maintainer line of rice

Abstract: DRR17A is a stable wild-abortive cytoplasmic male sterile line with medium-slender grain type. DRR17A and its maintainer line DRR17B are highly susceptible to two of the major rice diseases, bacterial blight (BB) and blast. To improve DRR17B for resistance against BB and blast, we have introgressed a major dominant gene each conferring resistance against BB (Xa21) and blast (Pi54) into CH Balachiranjeevi, S. Bhaskar Naik, V. Abhilash and R. M. Sundaram have contributed equally to this work.Electronic supplemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 50 publications
5
21
0
Order By: Relevance
“…In this study, the recurrent parent genome recovery rates in BC 1 F 1 , BC 2 F 1 and BC 2 F 2 were 73.8%, 83% and 84.7% (Figure 2), respectively. Compared with the theoretical %RPG, a relatively low background recovery rate was obtained, however, the results were consistent with those found in previous studies [36,37]. Marker-assisted backcrossing can accelerate the breeding process and facilitate a speedy recovery for most of the recurrent genome within a few generations [38], however, the population size of each backcross generation, linkage drag, number of background markers used and genetic background between two parents are considered to be factors that reduce the efficiency of MAB and %RPG [32].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In this study, the recurrent parent genome recovery rates in BC 1 F 1 , BC 2 F 1 and BC 2 F 2 were 73.8%, 83% and 84.7% (Figure 2), respectively. Compared with the theoretical %RPG, a relatively low background recovery rate was obtained, however, the results were consistent with those found in previous studies [36,37]. Marker-assisted backcrossing can accelerate the breeding process and facilitate a speedy recovery for most of the recurrent genome within a few generations [38], however, the population size of each backcross generation, linkage drag, number of background markers used and genetic background between two parents are considered to be factors that reduce the efficiency of MAB and %RPG [32].…”
Section: Discussionsupporting
confidence: 91%
“…The 80% and 89% recovery rates following two and three backcrosses were obtained from three-BB-gene-pyramided BC 2 and BC 3 genotypes, via MAS [35]. Balachiranjeevi et al (2015) transferred the BB gene, Xa21 and rice blast-resistant gene, Pi54, to DRR17A and were able to recover 73.4%, 84.8% and 93.4% RPG in the BC 1 , BC 2 and BC 3 generations, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…QTLs (A,a) qSBR11-1, (B,b) In this study, no positive or negative interactions were observed between genes conferring resistance against bacterial blight and blast. Similar results were found by Sundaram et al (2008) and Balachiranjeevi et al (2015). Singh et al (2014) also reported the incorporation of multiple disease resistance including BB, rice blast and ShB in Pusa 6B and developed the new stable improved lines of the Pusa 6B.…”
Section: R R R R R Rsupporting
confidence: 80%
“…Therefore, rice blast resistance has been considered as one of the priorities in the rice breeding program. R-gene linked or specific molecular markers were developed and widely used in the mainstream breeding programs via marker aided selection (MAS) (Jiang et al 2012;Balachiranjeevi et al 2015;Ni et al 2015;Shalini et al 2016;Wu et al 2016;Mi et al 2018). However, many rice blast R-gene haplotypes from different rice lines are almost identical except for a few nucleotide differences, leading to different specificities or even loss of function, e.g, different Pik and Pi2/9 alleles (Zhou et al 2007;Constanzo and Jia 2010).…”
Section: Discussionmentioning
confidence: 99%